PENGARUH ORIENTASI KEWIRAUSAHAAN, KEMAMPUAN MANAJEMEN, DAN STRATEGI BISNIS TERHADAP KINERJA USAHA (STUDI PADA UKM MEBEL DI SUMENEP) - Widyastuti, Endang; Firmansyah, Imam Darul (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Economic crisis result growth of economics which is slowly. Growth ofeconomics which is slowly non taking root at problem, because weakness at justmonetary and monetary sector, but weak of riil economic sector structure in faceof distortion from outside (external shock) or distortion from within (internalshock). Target of this research is to know influence entrepreneur orientation tocompany performance at UKM Furniture in Sumenep, to know influence ability ofmanagement to company performance at UKM Furniture Sumenep, to knowinfluence of business strategy to company performance at UKM FurnitureSumenep. Technique data analyse is used Doubled Linear Regression.